Comparison and Recommendations for Use of Dientamoeba fragilis Real-Time PCR Assays - Gough, Rory (J Clin Microbiol, 2019)
Dientamoeba fragilis is a gastrointestinal trichomonad parasite whose pathogenicity is yet to be determined. The difficulty involved in microscopically diagnosing D. fragilis in feces led to the development of real-time PCR methodologies for the detection of D. fragilis in stool samples. Prevalence studies in Europe show much higher levels of infection where a laboratory-developed real-time assay is the predominant assay for the detection of Dientamoeba fragilis than in regions that use the EasyScreen assay for detection of gastrointestinal pathogens. The aim of this study was to compare a commercially available Dientamoeba fragilis assay (Genetic Signatures EasyScreen assay) to a widely used laboratory-developed real-time PCR method. Two hundred fifty fecal samples were screened using the laboratory-developed real-time assay on four real-time PCR platforms producing a number of discrepant results. Limit-of-detection studies were undertaken to attempt to resolve sensitivity for each platform tested. The presence or absence of Dientamoeba fragilis DNA in discrepant samples was shown using PCR amplicon next-generation sequencing. Eukaryotic 18S diversity profiling was conducted on discrepant samples to identify the presence or absence of additional protozoan species in samples that may be responsible for cross-reactivity seen in these samples. The results revealed the potential for multiple false-positive results when using the laboratory-developed real-time assay across multiple real-time platforms using manufacturer default settings. This report provides recommendations to resolve these issues where possible and suggestions for future prevalence studies, and it emphasizes the EasyScreen assay as the molecular method of choice as well as the need for standardization of detection assays across all nations screening for D. fragilis.